Population size, provisioning frequency, flock size and foraging range at the largest known colony of Psittaciformes: The Burrowing Parrots of the north-eastern Patagonian coastal cliffs - Masello, Juan F. (2006)
Fil: Masello, Juan F.. Ecology of Vision Group. School of Biological Sciences. University of Bristol; UK